EMC² = comprehension: A reading strategy instruction framework for all teachers - Nanda M Klapwijk (South African Journal of Education, 2015)
Comprehension is a critical part of the reading process, and yet learners continue to struggle with it and teachers continue to neglect it in their teaching. Many reasons exist for the lack of focus on reading comprehension instruction, but for the most part, teachers simply do not seem to view comprehension as part of the reading process, are not able to teach the concept, and are seemingly not taught to do so during their teacher training years. In addition to this, comprehension continues to be viewed as part of 'language teaching', and is therefore viewed as the so-called 'language teacher's' domain. In support of effective comprehension instruction in the unique, multilingual South African education environment, this article proposes a framework for reading strategy instruction, aimed specifically at teachers. The framework was developed from a research study, and refined through subsequent application in a university course as well as a further study. The framework acknowledges that reading is a multifaceted and complex process, and accordingly, provides sufficient structure for teachers. It further addresses the issue of comprehension instruction through the use of selected reading strategies, designed to be applied by all teachers in all subjects in a flexible and easy manner.